Arginine Vasotocin, the Social Neuropeptide of Amphibians and Reptiles - Wilczynski, Walter; Quispe, Maricel; Muñoz, Matías I.; Penna, Mario (Frontiers in Endocrinology, 2017)
Arginine vasotocin (AVT) is the nonmammalian homologue of arginine vasopressin (AVP), and like vasopressin serves as an important modulator of social behavior in addition to its peripheral functions related to osmoregulation, reproductive physiology, and stress hormone release. In amphibians and reptiles the neuroanatomical organization of brain AVT cells and fibers broadly resembles that seen in mammals and other taxa. Both parvocellular and magnocellular AVT-containing neurons are present in multiple populations located mainly in the basal forebrain from the accumbens-amygdala area to the preoptic area and hypothalamus, from which originate widespread fiber connections spanning the brain with a particularly heavy innervation of areas associated with social behavior and decision making. As for mammalian AVP, AVT is present in greater amounts in males in many brain areas and its presence varies seasonally, with hormonal state, and in males with differing social status. AVT’s social influence is also conserved across herpetological taxa, with significant effects on social signaling and aggression, and, based on the very small number of studies investigating more complex social behaviors in amphibians and reptiles, AVT may also modulate parental care and social bonding when it is present in these vertebrates. Within this conserved pattern, however, both AVT anatomy and social behavior effects vary significantly across species. Accounting for this diversity represents a challenge to understanding the mechanisms by which AVT exerts its behavioral effects, as well are a potential tool for discerning the structure-function relationships underlying AVT’s many effects on behavior.